Balance between industry and agriculture in economic development (London, 1988)
This volume contains plenary addresses to the Eighth World Congress of the International Economic Association, held in Delhi. The authors are distinguished scholars from India, Japan, the Soviet Union, the United Kingdom and the United States. The basic issues treated in these papers are placed in an historical perspective in the second part of the volume, which deals with some of the economic theories in this subject area which were relevant in the past and assesses their relevance to the problems and policies of today and also analyses the historical development of economies to determine the lessons to be learnt for the current situation. The volume aims to represent a great diversity of viewpoints with representatives of socialist and underdeveloped states predominant.
Keywords: Economic development